The role of extracellular polymeric substances (EPS) in the reduction of Cr(VI) by Pannonibacter phragmitetus BB. Issue 5 (October 2021) - Wang, Yangyang; Liu, Yidan; Zheng, Kaixuan; Xie, Longfei; Ren, Qiang; Yang, Zhihui; Liao, Qi; Wang, Yulong; Chen, Runhua
Abstract: Cr(VI) contamination is a worldwide environmental problem, and bacterial reduction is considered a promising method for Cr(VI) remediation. In the present study, the role of extracellular polymeric substances (EPS) in the remediation of Cr(VI) by Pannonibacter phragmitetus BB was thoroughly studied. The results showed that the secretion of protein-fraction EPS by P. phragmitetus BB was significantly induced by Cr(VI), which increased from 382.70 to 1483.29 μg/mL with the increase of the initial Cr(VI) concentration (48–60 h). The polysaccharide content in slime EPS (SL-EPS) and loosely bound EPS (LB-EPS) increased gradually with time when the Cr(VI) concentration increased from 0 to 200 mg/L, with the highest polysaccharide content being higher than 2500 μg/mL. In contrast, the change in polysaccharides in tightly bound EPS (TB-EPS) was insignificant ( p  < 0.05). When the Cr(VI) concentration was higher than 200 mg/L, the secretion of polysaccharide-fraction EPS was inhibited (lower than 1000 μg/mL). Moreover, EPS removal inhibited the growth of P. phragmitetus BB and decreased Cr(VI) reduction efficiency. The adsorption capacity of intact cells to chromium was higher than that of EPS-free cells, which was fit with the Freundlich adsorption model with an R 2 value of 0.96. FTIR and XPS analyses demonstrated that intact cells had a higher adsorption capacity for Cr(VI) than EPS-free cells and that Cr(III) mainly existed as Cr2 O3, Cr(OH)3, CrCl3 or organic-Cr(III). In addition, the protein-fraction EPS had a critical role in Cr(VI) remediation, and the main functional groups were amine, carboxyl, hydroxyl and phosphate groups. Graphical abstract: ga1 Highlights: EPS ensured the growth of P. phragmitetus BB and its Cr(VI) reduction capacity. Cr(VI) induced the secretion of protein-fraction EPS. EPS enhanced the adsorption of chromium by P. phragmitetus BB. Intact cells have a higher adsorption capacity for Cr(VI) than EPS-free cells.